conflict at work (Journal of the College of Basic Education, 2023)
Praise be to God for His great blessings, and we thank Him as the one who acknowledges His bounty and his family, and may prayers and peace be upon him.On the elite of his prophets, his family, his companions and his saints..And after..The factors that make the action of the verb have their ruling in the conflict, and the conflict may occur between thesefactors in their modifiers, so that we can be clear, we must know that the working nounsThe ten verbs are:The infinitive - the subject's noun - the object's noun - the verbs of exaggeration - the adjective like a nounThe subject - the noun of the verb - the name of the infinitive - the approved adverb and adjective - the noun of preference.There may be multiple verbs or similar actions that perform their action, and each of the factors requires aMaamoul is specific to him, and there may not be in the speech except some maamouls that suffice the need of one of theseThe factors are not enough for each other, and those remaining factors continue to demand commissions of their own.Then these many factors crowd together over the few commissions, and conflict with each other, so that each one will be victorious.A worker with his work, and this is called conflict in work, or the door of deeds according to some grammariansthe old ones.Sibawayh referred to it in his classification of the chapters of the book, saying: ((This is the subject of the actorsAnd the two objects that each one of them does with its subject is like the one he does with it and what was towards that)).It is - then - directing two workers to any single agent that appears after them, requesting it in terms of effectiveness oreffectiveness, or both.- In our research for this section, we present a compilation of its material from what was available to us from the referenceSources This research is divided into three chapters and a conclusion.